2020
DOI: 10.3389/fcell.2020.594998
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ADF/Cofilin in Synaptic Physiology and Alzheimer’s Disease

Abstract: Actin-depolymerization factor (ADF)/cofilin, a family of actin-binding proteins, are critical for the regulation of actin reorganization in response to various signals. Accumulating evidence indicates that ADF/cofilin also play important roles in neuronal structure and function, including long-term potentiation and depression. These are the most extensively studied forms of long-lasting synaptic plasticity and are widely regarded as cellular mechanisms underlying learning and memory. ADF/cofilin regulate synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 278 publications
(488 reference statements)
0
50
0
Order By: Relevance
“…Its rearrangements by rapid assembly of actin monomers (G actin) to filaments (F actin) and inverse disassembly are essential for the formation of synaptic plasticity and long-term memory (Penzes, Rafalovich, 2012;Basu, Lamprecht, 2018). Disturbances in the mechanisms regulating the formation of F actin filaments and dendritic spine structure are thought to be associated with neurodegenerative disorders: Alzheimer's disease, schizophrenia, and autism (Bamburg, Bernstein, 2016;Borovac et al, 2018;Forrest et al, 2018;Ben Zablah et al, 2020;Lauterborn et al, 2020). Fig.…”
Section: The Actin Cytoskeleton and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Its rearrangements by rapid assembly of actin monomers (G actin) to filaments (F actin) and inverse disassembly are essential for the formation of synaptic plasticity and long-term memory (Penzes, Rafalovich, 2012;Basu, Lamprecht, 2018). Disturbances in the mechanisms regulating the formation of F actin filaments and dendritic spine structure are thought to be associated with neurodegenerative disorders: Alzheimer's disease, schizophrenia, and autism (Bamburg, Bernstein, 2016;Borovac et al, 2018;Forrest et al, 2018;Ben Zablah et al, 2020;Lauterborn et al, 2020). Fig.…”
Section: The Actin Cytoskeleton and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Together with cofilin phosphatases, LIMK1 regulates the balance of phosphorylated (inactive) and dephosphorylated (active) cofilin to control actin reorganization [20,21]. Perturbations of LIMK1 and cofilin have been shown to impair spine morphology, synaptic plasticity and memory, underscoring the crucial role of LIMK1/ cofilin signaling in synaptic and brain function [22][23][24][25]. Recent studies have also shown that abnormalities in both LIMK1 and cofilin are associated with AD patients and animal models of AD [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Perturbations of LIMK1 and cofilin have been shown to impair spine morphology, synaptic plasticity and memory, underscoring the crucial role of LIMK1/ cofilin signaling in synaptic and brain function [22][23][24][25]. Recent studies have also shown that abnormalities in both LIMK1 and cofilin are associated with AD patients and animal models of AD [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. For example, the level of phosphorylated cofilin was found to be decreased by the Aβ treatment as well as in the brain of AD mouse models [25,[28][29][30][31][32][33][34][35][36][37][38], suggesting that overactivation of cofilin may contribute to AD pathology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations